Relationships between microstructural features and mesoscopic fracture density in a Pleistocene till (Konin area, central Poland) - Włodarski, Wojciech (Bagucki Wydawnictwo Naukowe, 2010)
The qualitative and quantitative characteristics of microstructures in a till were analysed with SEM; it was also investigated whether the results depend on the till’s mesostructural characteristics. The till, exposed in a few open-cast browncoal mines near Konin in central Poland, is cut by numerous fractures which correspond to Riedel shear patterns, P-type structures and C-S type foliations. The fractures developed as a result of simple shearing induced by movement of the base of the Odranian ice sheet. On the basis of fracture density, two till types are distinguished: coarsely-brecciated till (wide spacing of fractures) and finely-brecciated till (closely spaced fractures). It is found that the fracture density is reflected in the microstructure of the till. The finely-brecciated till is characterised by a high porosity and has predominantly anisometric and fissure-like pores that also show a more clearly preferred orientation than the pores in the coarsely-brecciated till. In contrast, the coarsely-brecciated till has anisometric pores that show a less preferential orientation. The porosity of the coarsely-brecciated till is lower than in the finely-brecciated till. The finely-brecciated till probably represents a strongly deformed deposit, related in some cases to zones developed along thrusts that cut the till. Positive correlation between the porosity, the spatial arrangement of pores, and the density of fractures suggests a synsedimentary origin of the shear strain. This strain was accommodated by a particulate flow developed within both wide, pervasive zones and narrow, localised zones. The hydraulic conditions within the subglacial shear zone controlled rheological differences within the till during deformation and thus influenced the degree of the microstructure alteration.
Keywords: Till; Shear fractures; Microstructures; SEM; Rheology